New record of Chaptalia ignota Burkart (Asteraceae) for the Brazilian flora - Pasini, Eduardo; Ritter, Mara Rejane (Phytotaxa, 2012)
The first record of Chaptalia ignota (Asteraceae, Mutisieae) for the Brazilian flora is reported here. The species was found during a taxonomic and floristic revision of Chaptalia in the state of Rio Grande do Sul, Brazil. We provide updated taxonomic notes, an illustration and photographs of the species, and a distribution map.